2015
DOI: 10.4238/2015.december.29.42
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the association between polymorphisms in the interleukin-10 gene and risk of early-onset preeclampsia

et al.

Abstract: ABSTRACT. In this case-control study, we assessed the influence of IL-10 -1082A/G and -819T/C on the development of preeclampsia. The IL-10 -1082A/G and -819T/C polymorphisms were assessed by polymerase chain reaction-restriction fragment length polymorphism. The genotype distributions of the IL-10 -1082A/G and -819T/C polymorphisms in the control subjects were in conformance with Hardy-Weinberg equilibrium (HWE; P = 0.46 and 0.17). Unconditional logistic regression analyses revealed that individuals carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…Previous investigations have tested the association between IL-10 gene polymorphisms and preeclampsia development, but with conflicting results (Stonek et al, 2008;Vural et al, 2010;Valencia Villalvazo et al, 2012;Pissetti et al, 2014;Sowmya et al, 2014;Song and Zhong, 2015;Liu et al, 2015). Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous investigations have tested the association between IL-10 gene polymorphisms and preeclampsia development, but with conflicting results (Stonek et al, 2008;Vural et al, 2010;Valencia Villalvazo et al, 2012;Pissetti et al, 2014;Sowmya et al, 2014;Song and Zhong, 2015;Liu et al, 2015). Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al (2015) and Sowmya et al (2014) reported the IL-10 -819T/C genetic variant to be associated with increased preeclampsia risk in pregnant women in China and India. Similarly, in a study of 177 preeclamptic pregnant women and 182 controls, Song and Zhong (2015) found that the IL-10 -592A/C SNP elevated risk of early-onset preeclampsia in a Chinese population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Asian population, Liu et al. reported that the CC genotype of IL‐10‐819T/C enhanced the onset risk of PE in the Chinese population, while ‐1082A/G may not be related to the onset of PE 41 . Similar results were obtained in a case‐control study in India also demonstrating that ‐592A/C may be involved in the pathogenesis of PE 42 .…”
Section: Cytokines Involved In Th1/th2 Balancementioning
confidence: 59%
“…Three common polymorphisms of IL-4 were observed, including C-590T, C+33T and G-1098T. Although several recent studies have indicated that many polymorphisms of are involved in the pathogenesis of pre-eclampsia (Liu et al, 2015;Ren et al, 2016;Sun et al, 2016b;Tavakkol Afshari et al, 2016;Wang et al, 2016). However, only two studies have reported the association of IL-4 polymorphism with the development of pre-eclampsia so far (Fraser et al, 2008;Kang et al, 2014).…”
Section: Introductionmentioning
confidence: 97%